The use of cylindrical micro-wire electrodes for nano-impact experiments; facilitating the sub-picomolar detection of single nanoparticles - Ellison, J; Batchelor-McAuley, C; Tschulik, K; Compton, R (2014)
Electrochemical impact experiments can be used to detect and size single nanoparticles in suspension and at low concentrations. This is generally performed using a micro-disc working electrode; however, for the first time we report the use of cylindrical micro-wire electrodes for nanoparticle impact experiments. These electrodes provide much enhanced detection limits; specifically decreasing the concentration of nanoparticles measurable by over two orders of magnitude. In addition, the use of micro-wire electrodes reduces the shielding effect due to absorption of particles to the insulating sheath that surrounds a micro-disc electrode. Micro-wire electrodes are fabricated and their electrochemical response analysed via cyclic voltammetry experiments using molecular species. This provides a theoretical framework which is used to calculate the reduced concentration of nanoparticles required for an impact experiment at a micro-cylinder electrode in comparison to the micro-disc. Experimentally, it is demonstrated that impact experiments on the micro-cylinder electrodes can indeed be used for accurate characterisation of ultra-low concentrations (≈0.1 pM) of silver nanoparticles. © 2014 Elsevier B.V.